Abnormal quantum moment of inertia and structural properties of electrons in 2D and 3D quantum dots: an ab initio path-integral Monte Carlo study - Tobias Dornheim; Yangqian Yan (New Journal of Physics, 2022)
We present extensive new direct path-integral Monte Carlo results for electrons in quantum dots in two and three dimensions. This allows us to investigate the nonclassical rotational inertia (NCRI) of the system, and we find an abnormal negative quantum moment of inertia (2014 Phys. Rev. Lett. 112 235301) under some conditions. In addition, we study the structural properties by computing a re-normalized, angular-resolved center-two particle correlation function. Remarkably, we find no connection between the spatial structure and the NCRI, since the former can be nearly identical for Fermi- and Bose-statistics for parameters where the superfluid fraction is diverging towards negative infinity.